Wooden Drum Festival Suku Wa Di Ximeng Provinsi Yunnan - Riyana Istiqoma; Anita Amran; Tri Budianingsih (Universitas Al Azhar Indonesia, 2019)
Abstrak - Wooden Drum Festival adalah festival yang dirayakan oleh suku Wa di Yunnan, China. Festival ini dirayakan setiap tahunnya pada bulan November akhir atau Desember awal. Di antaranya ada tiga kegiatan utama yaitu Membuat dan Menarik Drum Kayu, Tarian Drum Kayu dan Sembahyang kepada Drum Kayu, serta terdapat pula kegiatan hiburan seperti perlombaan olahraga, pertunjukkan opera atau karnaval. Drum kayu adalah alat musik utama yang digunakan pada perayaan Wooden Drum Festival. Biasanya terbuat dari kayu merah dengan diameter 0,8 meter dan panjang sekitar 2 meter. Festival biasanya berlangsung selama tiga hari. Hingga saat ini festival ini masih terus dirayakan oleh suku Wa, karena mereka adalah suku yang sangat mematuhi ajaran agama.Abstract - Wooden Drum Festival is a festival celebrated by the Wa tribe in Yunnan, China. The festival is celebrated annually in late November or early December. Among them are three main activities, namely Making and Pulling Wooden Drums, Wooden Drum Dance and Worshiping Wooden Drums, and there are also entertainment activities such as sports competitions, opera shows or carnivals. Wooden drums are the main musical instruments used in the Wooden Drum Festival celebration. Usually made of red wood with a diameter of 0.8 meters and a length of about 2 meters. The festival usually lasts three days. Until now, the festival is still celebrated by the Wa tribe, because they are a tribe that strongly adheres to religious teachings.Keyword - China, Wa Autonomous Region, Wa Tribe, Wooden Drum Festival